An invisible ubiquitin conformation is required for efficient phosphorylation by PINK1. (13th November 2017) - Gladkova, Christina; Schubert, Alexander F; Wagstaff, Jane L; Pruneda, Jonathan N; Freund, Stefan MV; Komander, David
Abstract: The Ser/Thr protein kinase PINK1 phosphorylates the well‐folded, globular protein ubiquitin (Ub) at a relatively protected site, Ser65. We previously showed that Ser65 phosphorylation results in a conformational change in which Ub adopts a dynamic equilibrium between the known, common Ub conformation and a distinct, second conformation wherein the last β‐strand is retracted to extend the Ser65 loop and shorten the C‐terminal tail. We show using chemical exchange saturation transfer (CEST) nuclear magnetic resonance experiments that a similar, C‐terminally retracted (Ub‐CR) conformation also exists at low population in wild‐type Ub. Point mutations in the moving β5 and neighbouring β‐strands shift the Ub/Ub‐CR equilibrium. This enabled functional studies of the two states, and we show that while the Ub‐CR conformation is defective for conjugation, it demonstrates improved binding to PINK1 through its extended Ser65 loop, and is a superior PINK1 substrate. Together our data suggest that PINK1 utilises a lowly populated yet more suitable Ub‐CR conformation of Ub for efficient phosphorylation. Our findings could be relevant for many kinases that phosphorylate residues in folded protein domains. Synopsis: Phosphorylation of stably folded ubiquitin has been found to affect its conformational equilibrium. New NMR techniques reveal that unmodified ubiquitin also exists in two distinct conformational states, whose mutational stabilization differentially affects conjugation and phosphorylation reactions. A small population of wild‐type ubiquitin exhibits a C‐terminally retracted (Ub‐CR) conformation in Chemical Exchange Saturation Transfer (CEST)‐NMR experiments. Structure‐guided point mutations can shift the equilibrium in favor of either canonical or Ub‐CR conformation. Stabilization of the Ub‐CR conformation compromises ubiquitin conjugation reactions. The Ub‐CR conformation is a superior substrate for phosphorylation by the PINK1 kinase. Abstract : Unmodified ubiquitin protein exists in an equilibrium of two distinct conformational states, whose mutational stabilization differentially affects conjugation and phosphorylation reactions.